A Financial Stress Index for the Costa Rican Economy - Álvarez Corrales, Cristian (2016)
In this paper we present an Index of Financial Stress for the Costa Rican economy. This is a synthetic index constructed using weakly data from 20 variables of the Costa Rican financial system for the period July 2008 to March 2014. The method of aggregation used is principal components where financial stress is assumed to be the main driving force behind the co-movement observed between these variables. The index is aimed to be a contemporaneous measure of the degree of stress in the financial system and is expected to be part of the analytic tools available for policy makers in order to assess the stability of the Costa Rican financial system. The index constructed tracks reasonably well various episodes of financial turmoil experienced in Costa Rica, especially, the ones related to the international financial crisis of 2008, the european debt crisis of 2011-2012 and the period of high capital inflows in late 2012.